PROTECTION OF LAND RIGHTS HOLDERS IN LAND ACQUISITION FOR PUBLIC INTEREST IN NATIONAL DEVELOPMENT - Ginting, Andreas; Panjaitan, Hulman; Bethlen , Andrew (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Land acquisition for public needs is an activity to provide land by providing adequate and fair compensation, but in fact in the field there are still many people who do not agree with the nominal compensation for their land to be purchased for development in the public interest. Whereas in land acquisition there is the principle of social function for land rights to be used in accordance with their nature and purpose, it means that they must have benefits for right holders and the community. So that there is a need for a balance between individual interests and public interests for the community. Based on this, this research aims to find out and analyse the mechanism of land acquisition by the Land Bank Agency for land acquisition based on the UUCK and the juridical provisions for holders of land rights transferred for the public interest.This research is a normative juridical research with a statutory approach. The author uses secondary data using primary, secondary, and tertiary legal materials. The method of analysis used is qualitative method. This research concludes on the mechanism of land acquisition by the Land Bank Agency in Indonesia in accordance with Law No. 6 of 2023. The agency manages land for public interest and development in a transparent and non-profit manner. Its main tasks include planning, procuring, managing and distributing land, as well as planning licences and setting service rates. Land acquisition is conducted through several stages involving the public and the results are submitted to the Governor. If there are objections from the public, an evaluation is conducted. Landowners are entitled to fair compensation, and dispute resolution can be through the courts. The process must be fair and protect human rights by involving deliberation to reach an agreement.